Renal dysfunction after myocardial revascularization - Antunes, PE (2004)
OBJECTIVES: In this study, we evaluate the incidence of and analyse the pre and intraoperative risk factors for the development of postoperative renal dysfunction (PRD), and the impact of such an event on perioperative mortality and on hospital length of stay. In addition, we sought to investigate the influence of a mildly increased serum creatinine (1.3-2.0 mg/dl) on perioperative mortality and morbidity. METHODS: The study included 2445 consecutive patients who had no pre-existing renal disease (creatinine <or=2.0 mg/dl, without dialysis) and who underwent isolated coronary surgery under cardiopulmonary bypass between July 1996 and December 2001. The main outcome measure was PRD, defined as a postoperative serum creatinine level >or=2.1 mg/dl with a preoperative-to-postoperative increase >or=0.9 mg/dl. Univariate and multivariate analyses were performed where appropriate. RESULTS: Global 30-day mortality was 0.7%. The incidence of PRD was 5.6% (136 patients). Mortality for patients who experienced PRD was 8.8 vs. 0.1% for patients who did not (P<0.001). PRD increased the length of hospital stay by 3.4 days (7.6 vs. 11.0 days; P<0.001), and patients who needed haemodialysis (11%) had a perioperative mortality of 33.3% and a mean hospital length of stay of 16 days. Multivariable logistic regression identified the following variables as independent predictors of PRD: age (P=0.017; odds ratio (OR) 1.3 per 10 years), angina class III/IV (P=0.003; OR 1.7); cardiopulmonary bypass time (P=0.007; OR 1.01 per minute); preoperative serum creatinine levels: group 1 (1.3-1.6 mg/dl (P<0.001; OR 5.5)) and group 2 (1.7-2.0 mg/dl (P<0.001; OR 14.2)). Finally, a mild elevation of the preoperative creatinine level (1.3-2.0 mg/dl) increased significantly the probability of perioperative mortality, low cardiac output, haemodialysis and prolonged hospital stay. CONCLUSIONS: Although the likelihood of PRD in patients without pre-existing renal dysfunction is relatively low, it dramatically increases mortality, morbidity and length of stay after CABG. Mildly elevated (>1.2 mg/dl) preoperative serum creatinine level significantly increases the perioperative mortality and morbidity.